Capturing the 'expert's eye': A perspective on developing a better understanding and implementation of subjective performance evaluations in team sports. Issue 1 (2022) - Windt, Johann; Hamilton, Keith; Cox, David N.; Zumbo, Bruno D.; Sporer, Ben C.
No abstract available